Risk Management Committee Attributes and Market Performance of Listed Insurance Firms in Nigeria - Awotomilusi, Niyi Solomon; Ajoloko, Olatunde Matthew; Saka, Badmus Fatai; Adeniran, Taiwo Esther; Owonifari, Victor Olufemi; Dagunduro, Muyiwa Emmanuel (International Journal of Economics and Financial Issues, 2025)
This study aimed to examine how the attributes of risk management committees influence the market performance of listed insurance firms in Nigeria. This study adopted an expo-facto research design and data were collected from annual reports, financial databases of listed Nigerian insurance firms. The study population consisted of 23 insurance firms listed on the Nigerian Exchange Group (NGX) as of December 31st, 2023, with census sampling techniques applied to encompass the entire population. The research covered a 12-year period, spanning from 2012 to 2023, to provide robust analysis. The regression analysis results showed that certain attributes of the risk management committee such as its size, independence, and gender diversity positively and significantly impacted the market performance of listed insurance firms in Nigeria. Conversely, the frequency of risk committee meetings had a negative and significant effect on the market performance of these firms. The study concluded that a well-structured risk management committee with appropriate size, independence, and gender diversity can significantly enhance the market performance of insurance firms.